Urbanicity, behavior problems and HPA axis regulation in preschoolers - Effenberger, Pauline S.; Send, Tabea; Gilles, Maria; Wolf, Isabell A. C.; Frank, Josef; Bongard, Stephan; Kumsta, Robert; Witt, Stephanie; Rietschel, Marcella; Deuschle, Michael; Streit, Fabian (Psychoneuroendocrinology, 2022)
Growing up in cities is associated with increased risk for developing mental health problems. Stress exposure and altered stress regulation have been proposed as mechanisms linking urbanicity and psychopathology, with most research conducted in adult populations. Here, we focus on early childhood, and investigate urbanicity, behavior problems and the regulation of the hypothalamus-pituitary-adrenal (HPA) axis, a central circuit of the stress system, in a sample of N = 399 preschoolers aged 45 months. Urbanicity was coded dichotomously distinguishing between residences with more or less than 100,000 inhabitants. Behavior problems were measured using the Child Behavior Checklist (CBCL) 1½ - 5. Cortisol stress reactivity was assessed using an age-appropriated game-like stress task, and cortisol in the first morning urine was measured to assess nocturnal HPA axis activity. Urbanicity was not associated with behavior problems, urinary cortisol or the cortisol stress response. Neither urinary cortisol nor salivary cortisol response after stress exposure were identified as mediators of the relationship between urbanicity and behavior problems. The findings suggest no strong association of urbanicity with behavior problems and HPA axis regulation in preschool age. To our knowledge, this is the youngest sample to date studying the relationship between urbanicity and behavior problems as well as HPA axis regulation. Future research should examine at which age associations can first be identified and which mechanisms contribute to these relationships.